Vitamin D3 and seizure frequency in children with epilepsy using polypharmacy - Aprilyani, Setya Puspa Dewi; Putranti, Alifiani Hikmah; Sareharto, Tun Paksi; Rahmadi, Farid Agung; Pratiwi, Rina (Indonesian Pediatric Society, 2025)
Background Children with epilepsy usually need vitamin D administration, primarily due to the effects of antiepileptic drugs (AEDs). The use of AEDs, particularly polypharmacy, can reduce serum 25(OH)D levels. Vitamin D improves the function of neurotransmitters furthermore boosting the seizure threshold. There has been relatively little study investigating the effects of vitamin D3 treatment on seizure frequency. Objective To compare seizure frequency before and after administering vitamin D3 to the children with epilepsy who used polypharmacy. Methods Sixteen children with epilepsy and polypharmacy, aged 2-18 years, from the Pediatric Neurology Clinic, Dr. Kariadi Hospital, Semarang, were studied using a quasi-experimental approach with one group pretest-posttest. The vitamin D3 was given orally for two months with different dosages according to age andsubjects’ pretest serum 25(OH)D levels. Children with vitamin D insufficiency or deficiency were giventherapy dosage, and the normal vitamin D status were given supplementation dosage.Seizure frequency, serum 25(OH)D levels, and vitamin D status were assessed before and after treatment. Results Seizure frequency was significantly lower after vitamin D treatment for the entire group compared to pre- administration (P=0.019). For subjects with hypo-vitamin D levels pre-treatment, median seizure frequency was significantly decreased following normalization of vitamin D levels at one month (P=0.016) and two months (P=0.018) of vitamin D treatment. Using mean data, seizure frequency also significantly decreased at one month and at two months post-treatment. Conclusion Vitamin D3 administration is associated with an increase in serum 25(OH)D levels, as well as a decrease in seizure frequency. Vitamin D3 administration can significantly reduce seizure frequency in epilepsy patients undergoing polypharmacy who are vitamin D deficient.